Possible policy options to reduce the rice surplus in Korea - Yang, Tae-seon; Waibel, Hermann; Gartner, Joseph A.; Webster, Douglas R.; DAAD (Bangkok : Asian Institute of Technology, 1990)
Alternative rice policy options for Korea were investigated. The objective was to find suitable ways to reduce rice production , and to increase other crop production instead of rice under the physio-biological and socio-economic environment. Data collection was based on intensive interviews with individual farmers who were considered as representives for an agroecological zones viz . plain, semi-plain and hilly area. The study u sed linear programming as a tool to find an optimal Government ' s purchasing price by means of a sector .model based on representive farmers. The study mainly focussed on the entire agricultural sector of Korea. However, results are also useful for the individu al farmers because it demonstrates the impact of changing the Government ' s policies on the optimal allocation of farm resources.
A thesis submitted in partial fulfilment of the requirements of the degree of Master of Science, School of Environment, and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1990
Keywords: Agriculture and state -- Korea